Efficacy of cognitive training on executive functions in healthy older adults: a systematic review with meta-analysis of randomized controlled trials. - Olegário, Raphael Lopes; Fernandes, Sarah Ribeiro; de Moraes, Rui (Psychology & Health, 2025)
Objective: Systematically review randomized controlled trials on the efficacy of cognitive training on executive functions in healthy older people. Measures: The outcome measures were related to inhibitory control, working memory, and cognitive flexibility. Results: Thirty-one trials were included in the systematic review and thirteen trials in the meta-analysis. In the overall analysis, the cognitive training enhanced inhibitory control when measured by the Stroop task (p <.001, d = 1.64) and working memory when measured by the Corsi Block task (p =.002, d =.16). A marginal significance was found for working memory in the Digit Span task – Forward (p =.06, d =.92). However, cognitive training did not enhance inhibitory control when measured by the Go/No-Go task (p =.76, d =.59), working memory when measured by the Digit Span – Backward (p =.72, d =.95) and N-Back (p =.10, d =.26) tasks, and cognitive flexibility when measured by Trail Making – Part B (p =.08, d =.27) and Semantic Fluency (p =.49, d =.06) tasks. Conclusion: Mixed evidence was found for inhibitory control and working memory; cognitive flexibility showed no evidence of improvement.